2016
DOI: 10.1111/jfq.12249
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Heat‐Moisture Treated Proso Millet Flour in Production of Gluten‐Free Pound Cake

Abstract: Effect of heat‐moisture treatment of proso millet flour on the quality of gluten‐free cake was investigated. Millet flour was treated with two different moisture contents (20% and 30%) at two temperatures (100C and 120C), and then different amounts (0–100%) of treated flours were used in cake formulation. The physicochemical and sensory properties of batters and cakes containing treated flours were studied. Results showed that using of heat‐moisture treated flour decreased specific gravity and increased consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…• The panelists deemed unacceptable the inclusion of 100% pretreated proso millet flour in the cake recipe Fathi et al (2016) 3.…”
Section: Smentioning
confidence: 99%
“…• The panelists deemed unacceptable the inclusion of 100% pretreated proso millet flour in the cake recipe Fathi et al (2016) 3.…”
Section: Smentioning
confidence: 99%
“…Processing methods may improve product properties of baked goods, such as described for heat–moisture‐treated proso millet flour as ingredient in gluten‐free cakes (Fathi, Aalami, Kashaninejad, & Mahoonak, 2016). Four HMT conditions were compared, and except for the condition using the highest moisture (30%) and temperature (120°C) among the tested parameters, the cake volume increased, and crumbs became airier and softer.…”
Section: The Green Cluster: Quality Of Products With Proso Milletmentioning
confidence: 99%
“…Using a combination of untreated and heat–moisture‐treated proso millet flour resulted in better sensory ratings for parameters such as taste and texture, as well as overall acceptability than when only using heat‐treated proso millet flour. Thus, HMTs present a suitable processing operation to improve some product parameters, as long as the temperature and moisture are not too high (Fathi et al., 2016).…”
Section: The Green Cluster: Quality Of Products With Proso Milletmentioning
confidence: 99%
“…Likewise, Marston et al(2016) observed bread made by flour heated at 125°C for 30 min had larger specific volume and more cells per slice area. Fathi et al(2016) reported improvement in the volume, texture and colour of millet cake by heating at 100°C and 30% moisture on millet flour.…”
Section: Introductionmentioning
confidence: 99%
“…Scalding rye flour with boiling water significantly changed the crumb cell diameter, cell area, texture parameters and light reflectance of rye bread; it also could be applied to produce new colour and increase kinds and contents of volatile flavour compounds in baked products (Petersen et al, 2004;Esteller & Lannes, 2008). Fathi et al(2016) reported improvement in the volume, texture and colour of millet cake by heating at 100°C and 30% moisture on millet flour. Fathi et al(2016) reported improvement in the volume, texture and colour of millet cake by heating at 100°C and 30% moisture on millet flour.…”
Section: Introductionmentioning
confidence: 99%